Molecular methods for identification of clostridium tetani by targeting neurotoxin - Dharne, Mahesh S.; Nagoba, Basavraj S.; Gohil, Kushal N. (Methods Molecular Biology, 2017)
Tetanus is a potentially fatal muscle spasm disease. It is an important public health problem, especially in rural/tribal areas of developing countries. Tetanus toxin, a neurotoxin (tetanospasmin ), is the most important virulence factor that plays a key role in the pathogenicity of tetanus . Confirmation of virulence by confirming the production of tetanospasmin by infecting species forms the most important part in the diagnosis of tetanus . Various molecular methods have been devised for confirmation of diagnosis by targeting different genes. The most common molecular methods are tetanospasmin producing (TetX) gene-targeted methods using TetX-specific primers. Here, we describe various molecular methods targeting TetX gene such as polymerase chain reaction, pulsed-field gel electrophoresis, Southern blotting, loop-mediated isothermal amplification assay, etc. to confirm the virulence of Cl. tetani.